The Re-Islamization of Society and the Position of Women in Post-Soviet Uzbekistan. - Tokhtakhodzhaeva, Marfua (BRILL, 2008)
As well as being a valuable and insightful study into the history, development and tenets of Islam, with particular reference to life in Uzbekistan, this study, which draws on a wide personal network and extensive field research, is also in part a personal quest in support of women's position and aspirations in the modern world.